Relationship of performance measures and muscle activity between a 180° change of direction task and different countermovement jumps - Nygaard Falch, H.; Guldteig Rædergård, H.; van den Tillaar, R. (Sports, 2020)
The ability to rapidly perform change of direction (COD) is crucial for performance in Soccer. COD speed is thought to share similarities with countermovement jumps in kinematics and muscle activation. Thus, the objective of the current study was to investigate the relationship between muscle activities in performance measures of a modified 505-agility test and different countermovement jumps. Twenty-one experienced soccer players performed a COD test including the 505-agility test and uni- and bi-lateral horizontal and vertical countermovement jumps. The main findings were that the vertical bilateral and horizontal unilateral countermovement jump were able to predict total time to complete the COD, but not 505-agility time. Muscle activity in the COD and countermovement jumps was only distinguished by a higher peak muscle activity for the adductor longus, semitendinosus and biceps femoris in the COD to stabilize the hip and decelerate knee joint movements when turning compared with the jumps. Conclusively, the relationship between performance in countermovement jumps and total time to complete the COD test was due to longer sprint distances, which makes the distinction between performances bigger. Peak muscle activity of most muscles is similar between the jumps and the COD step, indicating similar muscular demands between these activities.